Protein kinase-A-dependent osteoprotegerin production on interleukin-1 stimulation in human gingival fibroblasts is distinct from periodontal ligament fibroblasts - Hormdee, D (Blackwell Science Inc, 2005)
Periodontitis, a chronic inflammatory disease, is characterized by increased expression of interleukin (IL)-1 and other inflammatory mediators resulting in extensive osteoclast formation and bone loss. Expression of receptor activator of nuclear factor kappa B ligand (RANKL) and its decoy receptor, osteoprotegerin (OPG), by osteoblasts is important to regulate osteoclast differentiation. The aim of the present study was to investigate the regulatory effects of IL-1 on RANKL and OPG production by mesenchymal fibroblasts in periodontal tissue. Human gingival fibroblasts (HGF) and periodontal ligament fibroblasts (PDL) were stimulated with IL-1α with or without protein synthesis inhibitor cycloheximide (CHX), protein kinase A (PKA) inhibitors, protein kinase C (PKC) inhibitors and prostaglandin E(2) (PGE(2)) inhibitor. In some experiments, the cultured cells were directly stimulated with either PKA or PKC activators. In HGF, IL-1α-stimulated OPG mRNA expression was high and could be reduced by CHX. PKA inhibitor completely abrogated IL-1α-induced OPG mRNA expression and OPG production. Endogenous PGE(2) further enhanced IL-1α-induced OPG production in HGF. In PDL, RANKL mRNA expression was greatly augmented by IL-1α. IL-1α induced OPG mRNA expression and protein production. PKC inhibitor partially reduced IL-1α-induced OPG production and PKC activator enhanced OPG production in PDL. The IL-1α-stimulated OPG mRNA expression in HGF was greater than PDL. These results provide new evidence for the possible osteoclastogenesis-inhibitory function of HGF through PKA activity pathway. PDL utilized PKC for OPG production. Thus, we emphasize that HGF and PDL have different characteristics of host defence mechanism against inflammatory process.